Penetapan Pengadilan sebagai Muara Dalam Penyelesaian Perkara Pidana di Luar Pengadilan Yang Menggunakan Pendekatan Restorative Justice - dewi, geney srikusuma (Fakultas Hukum Universitas Ngurah Rai, 2023)
estorative justice is a new approach in solving criminal cases. This approach emphasizes theinvolvement of the parties, whether victims, perpetrators, or related parties, with processes and goals thatseek recovery, and not just retaliation. The restorative justice (RJ) approach in practice in Indonesia wasfirst recognized within the scope of juvenile justice, but developments in the police, prosecutors also applythe RJ approach in the settlement of criminal acts that are resolved outside the court. The fact is that thearrangements in each of these institutions have different stages and their completion and supervision onlyinvolve one administering agency. Even though referring to the concept of an integrated criminal justicesystem that law enforcement agencies must have integration and synergy. So it becomes important whenthere is a settlement of a case using a restorative justice approach that is carried out outside the court toask for a court order to guarantee legal certainty. In the discussion it was found that the mechanism forimplementing the RJ has not yet been regulated in the form of a comprehensive regulation in the form of alaw so there is concern that it will have a level of disparity in its implementation. The results of this studyindicate that the settlement of criminal acts outside the court is regulated in the form of laws as in thejuvenile justice system and agreements for settlement of criminal acts must be determined in the form ofcourt orders.